2008
DOI: 10.1080/10463280801981645
|View full text |Cite
|
Sign up to set email alerts
|

Attributing and denying humanness to others

Abstract: We review a programme of research on the attribution of humanness to people, and the ways in which lesser humanness is attributed to some compared to others. We first present evidence that humanness has two distinct senses, one representing properties that are unique to our species, and the other-human nature-those properties that are essential or fundamental to the human category. An integrative model of dehumanisation is then laid out, in which distinct forms of dehumanisation correspond to the denial of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
199
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(216 citation statements)
references
References 41 publications
7
199
0
5
Order By: Relevance
“…In particular, Leyens et al (2000;2003) have repeatedly shown the infrahumanization effect, whereby participants attribute fewer secondary emotions (i.e. uniquely human emotions such as, pride, melancholy, shame, embarrassment, remorse, compassion) to outgroup members than to ingroupers (for a review, see Vaes, Leyens, Paladino, Pires, 2012; see also Haslam, Loughnan, Kashima, & Bain, 2008;Struch & Schwartz, 1989). However, while dehumanization represents one of the most robust forms of intergroup bias, little is known of the socio-cognitive processes that can inhibit this phenomenon.…”
Section: The Current Researchmentioning
confidence: 99%
“…In particular, Leyens et al (2000;2003) have repeatedly shown the infrahumanization effect, whereby participants attribute fewer secondary emotions (i.e. uniquely human emotions such as, pride, melancholy, shame, embarrassment, remorse, compassion) to outgroup members than to ingroupers (for a review, see Vaes, Leyens, Paladino, Pires, 2012; see also Haslam, Loughnan, Kashima, & Bain, 2008;Struch & Schwartz, 1989). However, while dehumanization represents one of the most robust forms of intergroup bias, little is known of the socio-cognitive processes that can inhibit this phenomenon.…”
Section: The Current Researchmentioning
confidence: 99%
“…One derives from the 'foreign-ness' of civilian casualties, which in turn contributes to their outgroup status (Rothbart and Korostelina 2006). Of the many studies of hostility against outgroups, some have highlighted infrahumanization -an implicit tendency to regard the outgroup as lacking some essentially human characteristics (Castano and Giner-Sorolla 2006;Haslam et al 2008) -as a mechanism by which the public might play down the cost and significance of civilian casualties. A final reason for expecting limited public responsiveness to civilian casualties is the phenomenon of proportional numbing, whereby people become "less sensitive to losses of life when those statistical losses are construed as small fractions of larger reference groups of at-risk individuals" (Friedrich andDood 2009, 2542).…”
Section: The Possibility Of Civilian Casualty Aversionmentioning
confidence: 99%
“…Meanwhile other perspectives emerged proposing that an adequate understanding of humanness-the quality that is denied to others when they are dehumanised-is necessary in order to get a full grasp of what it means to dehumanise others (Haslam, 2006 Haslam, Loughnan, Kashima, & Bain, 2008) systematically looked at the human concept from these perspectives and in this way distinguished between two senses of humanness. The first includes a set of core or central human attributes that involve emotionality, warmth, cognitive openness, agency, and depth, and is referred to as human nature.…”
Section: Differentiating Animalistic and Mechanistic Dehumanisationmentioning
confidence: 99%